Use of Artificial Intelligence in Journalism by Pakistani and Foreign Journalists - Yasin, Zaeem; Iqbal , Naveed; Islam , Ilsa (Journal of Peace, Development and Communication, 2021)
Artificial intelligence is a technology that has become prominent in our daily lives. It’s an innovative technology of the digital age which has change the pattern of many business sectors and media sector is not apart from it. Diffusion of Innovation is taken as theoretical support. This study identifies the use of artificial intelligence by both national and international journalists as well as threats and benefits of AI. To achieve the objectives this study uses qualitative method of in-depth interviews. First hypothesis “use of artificial intelligence enhance the working skills of journalists” second hypothesis “artificial intelligence plays a vital in changing traditional journalism to modern journalism”. Results revealed that artificial intelligence is being used by national and international journalists to enhance the quality of work but international media is one step ahead then national media. Still not every organization nationally and internationally has adopted the technology, it will take more time to use this technology evenly in every nation and organization. Keywords Artificial intelligence, journalism, technology, modernization, national and international journalists